Effects of robotic neurorehabilitation through lokomat plus virtual reality on cognitive function in patients with traumatic brain injury: A retrospective case-control study. (1st February 2020) - Maggio, Maria Grazia; Torrisi, Michele; Buda, Antonio; De Luca, Rosaria; Piazzitta, Denise; Cannavò, Antonio; Leo, Antonio; Milardi, Demetrio; Manuli, Alfredo; Calabro, Rocco Salvatore
Abstract: Background: Traumatic brain injury (TBI) is a clinical condition characterized by damage due to a mechanical physical event, which has a devastating impact on both the patient and his/her family. The purpose of this study is to evaluate the effects of robotic neurorehabilitation using Lokomat with virtual reality (VR) on attention processes and executive functions in patients with TBI. Materials and Methods: This is a retrospective case-control study. Fifty-six TBI patients have been included in the analysis, using an electronic recovery data system. The enrolled patients were divided into two groups: the experimental group (LPG) underwent rehabilitation training with Lokomat Pro, equipped with a VR screen, whereas the control group (LNG) performed rehabilitation training using Lokomat Nanos, without VR. The two groups matched for age, sex, education, brain lesions, interval from TBI. The rehabilitation protocol consisted of a total of 40 training sessions. Results: LPG and LNG had a significant improvement in mood and in the perception of physical well-being. However, only the LPG had a significant improvement in global cognitive, executive and attention functions. Furthermore, LPG presented a significant enhancement of the quality of life, with regard to the perception of the mental and physical state. Conclusion: Our study supports the idea that Lokomat is a useful tool in the rehabilitation of patients with TBI; in particular, the integration of the VR device can implement the cognitive and behavioral functions of TBI patients, enhancing also their physical and mental well-being.